2011
DOI: 10.14295/ras.v25i1.12978
|View full text |Cite
|
Sign up to set email alerts
|

Identificação De Célula De Fluxo Local No Sistema Aqüífero Guarani: Estudo De Caso No Vale Do Rio Taquari, Rs, Brasil.

Abstract: RESUMONa região do vale do Rio Taquari, RS, Brasil, o Aqüífero Botucatu, topo do Sistema Aquífero Guarani (SAG), foi investigado quanto ao modelo conceitual de circulação, por meio da integração de dados derivados da caracterização hidrogeológica de detalhe em uma ocorrência de água mineral (2 poços), do levantamento estratigráfico/estrutural em escala regional e, da reinterpretação de dados litológicos e hidroquímicos de 16 poços destinados ao abastecimento público. No sul do Brasil, a Zona de Falhas Dorsal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The Guarani Aquifer System (GAS) is one of the main water reservoirs in the world, occupying an area of 1,087,000 km² in the territories of Brazil, Uruguay, Argentina, and Paraguay. Despite being presented in its initial conception as a regionally homogeneous system, Hausmann (1995), Rosa Filho et al (2003), Machado (2005), Soares et al (2008), Giardin and Faccini (2011), among others, showed in the last decades that the GAS present great variability in its characteristics.…”
Section: Figure 1 -Study Area Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Guarani Aquifer System (GAS) is one of the main water reservoirs in the world, occupying an area of 1,087,000 km² in the territories of Brazil, Uruguay, Argentina, and Paraguay. Despite being presented in its initial conception as a regionally homogeneous system, Hausmann (1995), Rosa Filho et al (2003), Machado (2005), Soares et al (2008), Giardin and Faccini (2011), among others, showed in the last decades that the GAS present great variability in its characteristics.…”
Section: Figure 1 -Study Area Locationmentioning
confidence: 99%
“…In the northeastern region of RS, the GAS is characterized by granular aquifers ranging from unconfined to confined, which according to Machado (2005) and Giardin and Faccini (2011) belong to different Hydrostratigraphic Units (Botucatu, Pirambóia, Passo das Tropas, Alemoa, and Sanga do Cabral) and is limited at the top in almost all the area by volcanic rocks of the Serra Geral Group.…”
Section: Figure 1 -Study Area Locationmentioning
confidence: 99%